Workshop on Educational Innovation in Architecture: JIDA'17 5th Edition - Berta Bardí-Milà; Daniel García-Escudero; Beatriz Amante García; María Martínez Martínez (OmniaScience, 2018)
Workshop on Educational Innovation in Architecture (JIDA, http://revistes.upc.edu/ojs/index.php/JIDA) are a meeting point for professionals in teaching innovation in the field of Architecture. Its main aim is to present and share teaching experiences within several architecture disciplines. In this sense, the conference becomes a forum to discuss issues related to the daily pedagogical practice from a wide range of views both from national and international schools of Architecture. JIDA'17 goal is to improve the quality of learning in this specific field of knowledge and, more precisely, in the general training of architects. The five editions so far (2013-2017) have been developed under the initiative and coordination of the Grup per la Innovació i la Logística Docent en Arquitectura (GILDA), in cooperation with the Institut de Ciències de l'Educació (ICE-UPC). In the current monograph, we have included four communications which were presented in JIDA'S fifth edition (2017), and a preface by the Conference directors in which we discuss the global panorama of education in architecture in terms of teaching experiences collected in all previous JIDA's proceedings.